The effects of various work-to-rest ratios during high-intensity intermittent exercises on uchi-komi performance and postexercise heart rate and blood lactate in judo athletes - Ceylan, B.; Balci, S. S. (The Journal of Strength and Conditioning Research, 2023)
Uchi-komi exercises are the most important component of judo training. This study aimed to investigate the effect of different rest intervals during high-intensity intermittent uchi-komi exercises on total technique repetitions and physiological load in judo athletes. Twenty-two male judo athletes (mean age 19.0 ± 1.2 years, judo experience 7.6 ± 22.7 years) voluntarily participated in this study. Athletes' body composition and judo-specific performance were determined. The athletes randomly performed 20 seconds × 8 sets of high-intensity intermittent exercise using ippon-seoi-nage technique with 1:1/2, 1:1, 1:2, and 1:3 work-to-rest ratios on separate days. Before and 1, 7, 15, and 30 minutes after each exercise, athletes' heart rate (HR) and blood lactate were determined. The number of repetitions differed according to rest durations, when the rest duration decreased, the number of the repetitions decreased (F21, 441 = 7.09, p < 0.001). Blood lactate responses were similar during the exercises with different rest intervals (F3,63 = 2.15, p = 0.10). The shorter the rest duration, the higher the HR (F3,63 = 6.81, p < 0.001). The current study proposed that 1:2 and 1:3 work-to-rest ratios at high-intensity intermittent uchi-komi exercise are the most appropriate intervals to ensure a high number of technique repetitions and the continuity of the training.